Atención ginecológica de lesbianas y bisexuales: notas sobre el estado de situación en Argentina - Brown, Josefina Leonor (2014)
This paper presents results from a qualitative study on emerging issues within sexual and reproductive health, in which the aim was to describe the experiences of non-heterosexual women in relation to sexual and reproductive healthcare services. The objective was to identify and analyze perceptions of obstacles and facilitators of access to healthcare services. Eighteen semi-directed interviews were conducted with non-heterosexual women. The main result was that the specific obstacle to access to sexual and reproductive healthcare among these non-heterosexual women derived from a “logic of invisibility” among this population as gynecological patients, which resulted in anticipated discrimination (sensed discrimination) within a homo/lesbophobic context; absence of theoretical production and practical interventions regarding health and sex between women; and invisibility of lesbians and bisexuals as a group